Advances in the integrated recovery of valuable components from titanium-bearing blast furnace slag: A review - Cheng, Shaokai; Li, Wenbo; Vaughan, James; Ma, Xiaodong; Chan, Junxiang; Wu, Xuankun; Han, Yuexin; Peng, Hong (Sustainable Materials and Technologies, 2025)
Titanium-bearing blast furnace slag (TBFS) contains valuable elements such as titanium, aluminum, iron, and magnesium. Its storage occupies land and causes environmental pollution, so the integrated recovery of titanium and multi-elements from TBFS has received widespread attention. This article reviews the recent advanced processes for the recovery of titanium and other valuable components from TBFS, and illustrates the reaction mechanisms and characteristics of typical processes. The current methods for extracting titanium primarily involve carbonization-chlorination, acid leaching, alkali fusion, ammonium sulfate roasting, preparation of titanium alloys, as well as selective crystallization and separation. Among these, acid leaching, alkali roasting, and ammonium sulfate roasting allow for the titanium extraction and valuable components recovery, while other processes have yet to address the comprehensive recovery of TBFS. Corrosive reagents, high energy consumption, low extraction rate, and secondary slag emissions are challenges to conventional approaches. As a result, only the carbonization followed by chlorination process is applied in industry. Subsequently, it was envisioned that the future TBFS treatment processes should take into account the development of low-carbon and green titanium extraction methods, comprehensive recovery of other valuable elements, and the exploration of additional value products. [Display omitted]